2014
DOI: 10.1016/j.bse.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of Lonicera japonica with related species: Morphological characteristics, ITS sequences and active compounds

Abstract: a b s t r a c tMorphological characteristics, ITS sequences, and active compounds have been used to differentiate between species of Lonicera used in the traditional Chinese medicines Flos Lonicerae Japonicae (FLJ) and Flos Lonicerae (FL). FLJ includes L. japonica whereas FJ includes Lonicera macranthoides, Lonicera hypoglauca, Lonicera confusa and Lonicera fulvotomentosa. FLJ could be distinguished from FL using four quantitative and 10 qualitative characters, ITS sequences, chlorogenic acid and luteoloside c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…The amounts of luteoloside are remarkably lower in flower buds of L. hypoglauca than inthose of L. japonica , whereas no obvious change is observed between the flower buds of L. japonica and L. macranthoides [ 8 ]. However, according to the description in the Chinese pharmacopoeia 2010 and the view reported by Wu et al [ 7 ], luteolin and luteoloside are in lower abundance in flower buds of L. macranthoides than in those of L. japonica [ 33 ]. In the present study, luteoloside accumulation initially increased from stage 2 to stage 4 and then decreased in stage 5 during flower development in L. macranthoides ( Figure 1 F), which is in accordance with the results of previous reports in L. japonica [ 1 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The amounts of luteoloside are remarkably lower in flower buds of L. hypoglauca than inthose of L. japonica , whereas no obvious change is observed between the flower buds of L. japonica and L. macranthoides [ 8 ]. However, according to the description in the Chinese pharmacopoeia 2010 and the view reported by Wu et al [ 7 ], luteolin and luteoloside are in lower abundance in flower buds of L. macranthoides than in those of L. japonica [ 33 ]. In the present study, luteoloside accumulation initially increased from stage 2 to stage 4 and then decreased in stage 5 during flower development in L. macranthoides ( Figure 1 F), which is in accordance with the results of previous reports in L. japonica [ 1 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Past research has isolated 140 organic compounds from L. japonica , including essential oils, flavonoids, organic acids, and triterpene glycosides (Kuroda, Shizume, & Mimaki, ; Shang, Pan, Li, Miao, & Ding, ). Recent studies have shown that extracts from L. japonica have a wide range of bioactive properties, such as anti‐inflammatory (Chen, Liou, Tzeng, Lee, & Liu, ), antibacterial (Xiong et al, ), and antioxidant use (Wang et al, ), and are used to treat nephrotic diabetes (Tzeng, Liou, Chang, & Liu, ) and metabolic diseases (Shin et al, ). Tyrosinases (EC1.14.18.1), one of the extracts from L. japonica , are metalloenzymes belonging to the type‐3 (binuclear) copper protein (Rolff, Schottenheim, Decker, & Tuczek, ) that exist widely in microorganisms (Faccio, Kruus, Saloheimo, & Thony‐Meyer, ), animals (Hu, Wang, Deng, & Jiang, ), and plants (Zekiri et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, a gene that is closely related to the variation in the active components can be identified through a study of the functional gene, to provide a basis for further investigation into the genetic mechanisms behind variation in active components (Liu, 2006). Many recent studies on the correlation between gene polymorphisms and active components have suggested that active components are associated with geographical distribution and haplotypes (Li et al, 2011;Wang et al, 2014;Zhang et al, 2015). However, few studies have focused on the correlation between species and active components.…”
Section: Discussionmentioning
confidence: 99%